A proactive approach to ergonomics: an evaluation of multi-method risk assessment in warehouse operations - Ugurtay, Oguzhan; Korkmaz, Sonnur; Dalfidan, Derya; Gunduz, Tulin (Taylor & Francis Ltd, 2026)
The proactive use of ergonomic assessment methods enhances worker performance and health while improving task quality and reducing operational costs through human-centred work design. This study was conducted in a logistics warehouse, where 197 tasks across nine locations were evaluated using REBA, RULA, BAuA, and LMM-ZS. Data were collected through on-site observations and task-specific video recordings. Risk scores were normalised to a 0-100 scale to enable cross-method comparison. Multi-method evaluations create two main challenges: selecting the most suitable method for each task and integrating outcomes derived from incompatible scales. To address these issues, a harmonised framework is proposed that standardises score ranges and categorical zones across the four methods.
Keywords: Multi-method risk assessment; REBA; RULA; BAuA and LMM